EKSPLORASI DIMENSI PRAKTIK RELIGIUS REMAJA MUSLIM INDONESIA - Helli Ihsan; Sitti Chotidjah; Herlina , (Departemen Psikologi Universitas Pendidikan Indonesia, 2017)
The concept of Christian-Western religious practice maybe different to the Islamic religious practice of Moslems. Therefore, explores the dimensions of Daily Religious Practices of Moslems (Praktik Religius Harian Muslim) (Herlina et al., 2015) consisting of 10 items that proven able to predict juvenile delinquency is important to do. This measure was assumed to be unidimensional because is just intended to measure dimensions of religious practice. Principal Component Analysis is used to find dimensions or factors of this measure. The participants were 643 students of two public high schools, one private high school, one private Islamic High School, and one Islamic boarding high school. There were two practical dimensions that found in this PRHM scale, Obligatory Practice and Sunnah Practice. These results give different concept from Western religious theory which emphasizes public and private practices. Although Moslems practices can be private and public but the practices of Indonesian Moslems teenagers were patterned to two of this dimensions.AbstrakKonsep religiusitas Barat yang berbasis Kristen mungkin saja akan berbeda dengan religiusitas Indonesia yang berdasarkan Islam. Untuk itu mengekplorasi dimensi dalam alat ukur Praktik Religius Harian Muslim (PRHM) (Herlina dkk., 2015) yang terdiri dari 10 item dan yang terbukti mampu memprediksi kenakalan remaja ini penting untuk dilakukan. Metode Principal Component Analysis digunakan untuk menemukan dimensi atau faktor yang ada dalam alat ukur ini. Partisipan yang terlibat berjumlah 643 siswa dari dua SMA Negeri, satu SMA swasta umum, satu SMA Islam, dan satu SMA Islamboarding school atau pesantren. Ada dua dimensi praktik yang ditemukan dalam alat ukur PRHM ini yaitu Ibadah Wajib dan Ibadah Sunnah. Meskipun praktik muslim bisa bersifat privat dan publik tapi praktik remaja muslim Indonesia lebih berpola kepada Ibadah Wajib dan Ibadah Sunnah.